Characterization of changes in intrahepatic immune cell populations during HCV treatment with sofosbuvir and ribavirin. Issue 3 (3rd December 2018) - Orr, Cody; Aartun, Johannes; Masur, Henry; Kottilil, Shyam; Meissner, Eric G.
Summary: Treatment of chronic hepatitis C virus (HCV) infection with direct‐acting antivirals (DAAs) results in a sustained virologic response (SVR) in most patients. While highly efficacious, 3%‐5% of patients do not achieve SVR despite having virus that appears susceptible. It is unclear whether host factors contribute to treatment failures, although innate and adaptive immunity may play a role. Previous studies showed that after DAA treatment, the composition of intrahepatic immune cells does not normalize relative to healthy volunteers, even in cases where SVR is achieved. We used paired pre‐ and post‐treatment liver biopsies from 13 patients treated with sofosbuvir and ribavirin, 4 of whom relapsed, to analyse intracellular immune changes during DAA treatment and explore correlations with inflammation and treatment outcome. We performed single marker immunohistochemistry followed by electronic image capture, manual annotation of parenchymal and non‐parenchymal regions, and quantitative image analysis. The predominant cellular change during treatment was a decrease in CD8+ cellular density in both parenchymal and non‐parenchymal regions. CD68+ Kupffer cell density correlated with hepatic inflammation (AST, ALT) pre‐treatment, but did not change during treatment. CD4+ cellular density decreased in non‐parenchymal regions and, intriguingly, was lower pre‐treatment in subjects who eventually relapsed. Other cellular markers (CD56, CD20), as well as markers of apoptosis (TIA‐1) and activated stellate cells, did not change significantly during treatment or differ by treatment outcome. The predominant intrahepatic cellular change during DAA treatment of chronic HCV infection is a reduction in CD8+ cellular density, but this did not correlate with treatment outcome.